The systematic status of two enigmatic ocypodoid crabs, "Paracleistostoma" dentatum Tesch, 1918, and " Paracleistostoma" fossulum Barnard, 1955 (Crustacea: Decapoda: Brachyura) - Ng, P.K.L. (2014)
Zootaxa